The isospin structure of photoproduction of πη pairs from the nucleon in the threshold region; Physics Letters B; Vol. 748 - Käser A.; Ahrens J.; Annand J. R. M.; Arends H. J.; Bantawa K.; Bartolome P. A.; Beck R.; Bekrenev V.; Berghäuser H.; Braghieri A.; Branford D.; Briscoe W. J.; et al. (2015, 2015)
Title screen